DOI: 10.31274/etd-180810-4484
|View full text |Cite
|
Sign up to set email alerts
|

Languaging in cyberspace: a case study of the effects of peer-peer collaborative dialogue on the acquisition of English idioms in task-based synchronous computer-mediated communication

Abstract: I dedicated this dissertation to my father Jiuwu Teng and my mother Tiantian Huang, whose love, support, and encouragement have kept me moving forward in my doctoral study. iii TABLE OF CONTENTS LIST OF FIGURES .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 170 publications
3
2
0
Order By: Relevance
“…Certainly, it means that EFL students are aware of the beneficial co-construction of the passage comprehension with reliable peers. This result matches the findings of Al-Roomy (2013) and Teng (2015). Additionally, the results indicated that the students elevated their confidence and readiness level by expressing and sharing their ideas freely with their peers within the SCMC environment (Statements 2.2, 2.4 and 2.6).…”
Section: Discussion Of the Results Related To The Second Research Quesupporting
confidence: 88%
See 4 more Smart Citations
“…Certainly, it means that EFL students are aware of the beneficial co-construction of the passage comprehension with reliable peers. This result matches the findings of Al-Roomy (2013) and Teng (2015). Additionally, the results indicated that the students elevated their confidence and readiness level by expressing and sharing their ideas freely with their peers within the SCMC environment (Statements 2.2, 2.4 and 2.6).…”
Section: Discussion Of the Results Related To The Second Research Quesupporting
confidence: 88%
“…Additionally, the results indicated that the students elevated their confidence and readiness level by expressing and sharing their ideas freely with their peers within the SCMC environment (Statements 2.2, 2.4 and 2.6). Similar results are reported in Al-Jadoa (2016), Nejad and Keshavarzi (2015) and Teng (2015), who suggest that collaboration with peers within SCMC reduces nervousness and boosts self-esteem, which in turn, is reflected in greater reading performance. Lastly, the students favored the collaborative dialogue in text-based SCMC over face-to-face communication, as they found it beneficial to accomplish better reading performance.…”
Section: Discussion Of the Results Related To The Second Research Quesupporting
confidence: 84%
See 3 more Smart Citations